Peptide‐Based Biomarker Discovery for Identification of Rice Cultivars using Surface Enhanced Laser Desorption/Ionization Time‐of‐Flight Mass Spectrometry. Issue 3 (1st May 2013) - Park, Sei Joon; Lee, Yong Ho; Nam, Yun Jung; Baik, Byung‐Kee; Kim, Tae Wan
ABSTRACT: Biomarkers of desirable traits are important for selection of elite lines in multigeneration breeding processes. To develop peptide‐based biomarkers for rice ( Oryza sativa L.) genotype identification, we applied surface enhanced laser desorption/ionization (SELDI) time‐of‐flight (TOF), a mass spectrometry (MS) technique. Dehusked rice of 'Ilpumbyeo' was compared with two rice cultivars, Goami‐2, which was mutagenized for development of high amylose and selected from Ilpumbyeo, and Goami‐3, which originated from Goami‐2. In the molecular range from 2000 to 25, 000 Da, the three cultivars exhibited significant differences in peak intensity ( p < 0.01) for 13 peptides on CM10 (weak cation exchange) and 31 peptides on Q10 (strong anion exchange). Heat mapping via supervised hierarchical clustering on the peptides showing significant differences between the three cultivars at p < 0.01 effectively distinguished cultivars and categorized these peptides into seven groups. Considering the peaks with high intensity and low probability among the cultivars, peptides of 2621, 3498, 3801, and 7854 Da for Ilpumbyeo, those of 7547 and 8889 Da for Goami‐2, and that of 11, 560 Da for Goami‐3 were selected as potential biomarkers for rice genotype identification. Our work suggests that distinguished peptides of rice cultivars could be detected using SELDI‐TOF MS, which has advantages in profiling of low molecular peptides, and used as biomarkers for cultivar identification.